The invention of Judaism: Torah and Jewish identity from Deuteronomy to Paul - Collins, John J. (The Taubman lectures in Jewish studies, 2017)
"Judaism is often understood as the way of life defined by the Torah of Moses, but it was not always so. This book identifies key moments in the rise of the Torah, beginning with the formation of Deuteronomy, advancing through the reform of Ezra, the impact of the suppression of the Torah by Antiochus Epiphanes and the consequent Maccabean revolt, and the rise of Jewish sectarianism. It also discusses variant forms of Judaism, some of which are not Torah-centered and others which construe the Torah through the lenses of Hellenistic culture or through higher, apocalyptic, revelation. It concludes with the critique of the Torah in the writings of Paul"--Provided by publisher